Association between long-term exposure to PM2.5 chemical components and metabolic syndrome in middle-aged and older adults - Zhang, Jingjing; Zhang, Jinglong; Duan, Zhizhou; Nie, Jing; Li, Xiangyu; Yu, Wenyuan; Niu, Zhiping; Yan, Yangjin (Frontiers in Public Health, 2024)
Background: Previous studies indicated that exposure to ambient fine particulate matter (PM2.5) could increase the risk of metabolic syndrome (MetS). However, the specific impact of PM2.5 chemical components remains uncertain. Methods: A national cross-sectional study of 12,846 Chinese middle-aged and older adults was conducted. Satellite-based spatiotemporal models were employed to determine the 3-year average PM2.5 components exposure, including sulfates (SO42-), nitrates (NO3–), ammonia (NH4+), black carbon (BC), and organic matter (OM). Generalized linear models were used to investigate the associations of PM2.5 components with MetS and the components of MetS, and restricted cubic splines curves were used to establish the exposure-response relationships between PM2.5 components with MetS, as well as the components of MetS. Results: MetS risk increased by 35.1%, 33.5%, 33.6%, 31.2%, 32.4%, and 31.4% for every inter-quartile range rise in PM2.5, SO42-, NO3-, NH4+, OM and BC, respectively. For MetS components, PM2.5 chemical components were associated with evaluated risks of central obesity, high blood pressure (high-BP), high fasting glucose (high-FBG), and low high-density lipoprotein cholesterol (low-HDL). Conclusion: This study indicated that exposure to PM2.5 components is related to increased risk of MetS and its components, including central obesity, high-BP, high-FBG, and low-HDL. Moreover, we found that the adverse effect of PM2.5 chemical components on MetS was more sensitive to people who were single, divorced, or widowed than married people.